Controlling the Production of Acid Catalyzed Products of Furfural Hydrogenation by Pd/TiO2. Issue 24 (2nd November 2021) - Tierney, George F.; Alijani, Shahram; Panchal, Monik; Decarolis, Donato; de Gutierrez, Martha Briceno; Mohammed, Khaled M. H.; Callison, June; Gibson, Emma K.; Thompson, Paul B. J.; Collier, Paul; Dimitratos, Nikolaos; Corbos, E. Crina; et al.
Abstract: We demonstrate a modified sol‐immobilization procedure using (MeOH)x /(H2 O)1‐x solvent mixtures to prepare Pd/TiO2 catalysts that are able to reduce the formation of acid catalyzed products, e. g. ethers, for the hydrogenation of furfural. Transmission electron microscopy found a significant increase in polyvinyl alcohol (PVA) deposition at the metal‐support interface and temperature programmed reduction found a reduced uptake of hydrogen, compared to an established Pd/TiO2 preparation. We propose that the additional PVA hinders hydrogen spillover onto the TiO2 support and limits the formation of Brønsted acid sites, required to produce ethers. Elsewhere, the new preparation route was able to successfully anchor colloidal Pd to the TiO2 surface, without the need for acidification. This work demonstrates the potential for minimizing process steps as well as optimizing catalyst selectivity – both important objectives for sustainable chemistry. Abstract : Furfural hydrogenation : The use of MeOH solvent mixtures in the preparation of Pd/TiO2 catalysts through sol‐immobilization limits the formation of acid catalyzed ether products for the hydrogenation of furfural; it is proposed that this is achieved through the additional clustering of PVA around the metal surface, which hinders hydrogen spillover to form surface hydroxyls.